Catalytically inactive carbonic anhydrase‐related proteins enhance transport of lactate by MCT1 - Ashok Aspatwar; Martti E. E. Tolvanen; Hans‐Peter Schneider; Holger M. Becker; Susanna Narkilahti; Seppo Parkkila; Joachim W. Deitmer (FEBS Open Bio)
Carbonic anhydrases (CA) catalyze the reversible hydration of CO2 to protons and bicarbonate and thereby play a fundamental role in the epithelial acid/base transport mechanisms serving fluid secretion and absorption for whole‐body acid/base regulation. The three carbonic anhydrase‐related proteins (CARPs) VIII, X, and XI, however, are catalytically inactive. Previous work has shown that some CA isoforms noncatalytically enhance lactate transport through various monocarboxylate transporters (MCT). Therefore, we examined whether the catalytically inactive CARPs play a role in lactate transport. Here, we report that CARP VIII, X, and XI enhance transport activity of the MCT MCT1 when coexpressed in Xenopus oocytes, as evidenced by the rate of rise in intracellular H+ concentration detected using ion‐sensitive microelectrodes. Based on previous studies, we suggest that CARPs may function as a ‘proton antenna’ for MCT1, to drive proton‐coupled lactate transport across the cell membrane.